Pengembangan Model Logistik Terpadu untuk Peningkatan Efisiensi Transportasi Barang - Pradina, Alia Ingrid (Peneliti.net, 2025)
This research aims to develop an integrated logistics model that can improve the efficiency of goods transportation in Indonesia. The proposed model will include aspects of technology, management, and public policy to create a responsive, flexible, and sustainable logistics system. This research will use a literature study approach to develop an integrated logistics model that aims to improve the efficiency of goods transportation. Research on logistics efficiency in Indonesia resulted in an integrated model that utilizes information technology to optimize freight transportation. The model reduces waiting time and delivery errors, and introduces “Green Logistics” to reduce environmental impact. Information system integration and route optimization improved responsiveness and efficiency. Inter-company collaboration and big data analysis support better resource planning. Environmental sustainability is emphasized to reduce carbon footprint and improve corporate image.